The Association Between Demographic, Mental Health, and Intimate Partner Violence Victimization Variables and Undergraduate Women’s Intimate Partner Violence Perpetration - Holmes, Samantha C. (Journal of interpersonal violence, 2022)
Addressing women’s intimate partner violence (IPV) perpetration is essential not only to their partners’ safety but also to their own as, for women who are victims of IPV, their IPV perpetration may be a risk factor for their own revictimization. Although many studies have examined risk factors for women’s IPV perpetration, results diverge with regard to whether demographic and mental health variables are reliable predictors. Results of several studies have demonstrated that when IPV victimization is examined concurrently with perpetration, demographic and mental health variables are no longer significant correlates. However, this research has been limited in that the type of IPV examined has been restricted to physical, psychological, and sexual abuse. In addition, some demographic variables (e.g., sexual orientation) have yet to be adequately examined. The current study extends this literature by concurrently assessing demographic, mental health, and IPV victimization variables as correlates of IPV perpetration among undergraduate women. Furthermore, the current study examined a wide range of IPV types (i.e., threats of physical abuse, physical abuse, sexual abuse, psychological maltreatment, stalking, cyberstalking). Among a final sample of 398 undergraduate women at a Midwestern public university, results demonstrated that while all variables (i.e., demographic, mental health, IPV victimization) were correlated with at least one type of IPV perpetration, only IPV victimization remained a unique significant correlate of perpetration for each of the six IPV perpetration types when variables were analyzed concurrently in hierarchical regression models. Demographic and mental health variables were nonsignificant correlates for most IPV perpetration types. These results corroborate previous studies and provide additional evidence that targeting women’s own victimization, safety planning, and de-escalation may be useful at decreasing violence against women’s partners as well as women’s own risk for revictimization.